Holding device

By using a conjugate with low thermal resistance and stable thermal conductivity in the holding device, the problem of low heat transfer efficiency and uneven temperature distribution of electrostatic chuck in strong plasma energy and high power applications is solved, achieving a faster and uniform cooling effect.

JP7656109B2Active Publication Date: 2025-04-02NITERRA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024022793
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-02-19
Publication Date
2025-04-02
Estimated Expiration
2042-06-14

AI Technical Summary

Technical Problem

In environments with strong plasma energy and high power applications, the heat transfer efficiency of the electrostatic chuck is low, resulting in insufficient cooling speed of the wafer mounting surface, and in extremely low temperature environments, the thermal conductivity changes greatly, resulting in uneven temperature distribution.

Method used

A holding device is designed which includes a plate-shaped base with cooling function, which is connected to the plate-shaped portion, and through a bond with low thermal resistance, it ensures that the thermal conductivity changes at very low temperatures and at normal temperatures are small.

Benefits of technology

By reducing the thermal resistance of the bond and improving the stability of the thermal conductivity, the cooling speed of the wafer mounting surface is improved and the unevenness of the temperature distribution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656109000001
    Figure 0007656109000001
  • Figure 0007656109000002
    Figure 0007656109000002
  • Figure 0007656109000003
    Figure 0007656109000003
Patent Text Reader

Abstract

To provide a technique capable of improving at least any one of a cooling speed of a side surface where an object is mounted and a uniformity of an in-surface temperature distribution of the side surface where the object is mounted in a retainer holding the object.SOLUTION: A retainer comprises: a plate-like part that is formed in a plate-like shape having a first surface on the side where an object is mounted and a second surface as a back surface of the first surface; a base part that is arranged onto the second surface side of the plate-like part, supports the plate-like part, includes a cooling function, and is formed in the plate-like shape; and a joint part that is arranged between the plate-like part and the base part, and joints the plate-like part and the base part. A heat resistance of the joint part is 1.1×10-3 (m2K / W) or less at the time of -60°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a retention device. [Background technology]

[0002] Conventionally, as a holding device for holding an object, for example, a wafer or the like in manufacturing semiconductors has been used. Electrostatic chucks for holding objects are known. Generally, electrostatic chucks have a structure in which an object is placed on the electrostatic chuck. a plate-like portion in which the cooling medium is inserted, a base portion in which a coolant flow path is formed, and a joining portion for joining the plate-like portion and the base portion. For example, Patent Documents 1 and 2 disclose a method for manufacturing a bonding material layer (bonding portion) using silicone. Thermally conductive films such as silicone resin and aluminum oxide or aluminum nitride are used. It is described that an adhesive made of a composite resin containing a filler is used. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 4-287344 [Patent Document 2] JP 2014-207374 A Summary of the Invention [Problem to be solved by the invention]

[0004] In environments where the electrostatic chuck is exposed to strong plasma energy or where high power is applied to the electrostatic chuck When the device is used in an environment where a large amount of heat is input, the wafer mounting surface is likely to become hot. If the electrostatic chucks described in 1 and 2 are used in such an environment, the thermal conductivity of the adhesive layer will decrease. Since the conductivity is relatively low, there is a risk that the cooling rate of the wafer mounting surface may not be sufficient. In order to increase the cooling rate of the wafer mounting surface, it is desirable to improve the heat dissipation of the bonding portion. There are.

[0005] In addition, if the wafer mounting surface is prone to becoming hot as described above, a base plate is used to cool it down. Since the contact side is used at extremely low temperatures, the temperature difference between the top and bottom of the joint as well as within the surface is large. The silicone resins described in Patent Documents 1 and 2 have a large change in thermal conductivity in the low temperature range. Because of the existence of a temperature range, a temperature distribution occurs at the joint, which changes the thermal conductivity characteristics of the joint. If this is the case, there is a risk that the in-plane temperature distribution of the wafer-mounting surface of the electrostatic chuck will become increasingly non-uniform. Therefore, there is a demand for joints whose thermal conductivity changes little with temperature. These problems are not limited to electrostatic chucks, but also apply to semiconductor etching devices such as plasma etching devices. This is a common issue with various holding devices, such as manufacturing devices.

[0006] The present disclosure has been made to solve at least part of the above-mentioned problems, and In a holding device for holding an object, the cooling rate of the surface on which the object is placed and the A technology to improve at least one of the uniformity of the in-plane temperature distribution on the surface on which the substrate is placed The purpose is to provide. [Means for solving the problem]

[0007] The present disclosure can be realized in the following forms. (1) According to one aspect of the present disclosure, there is provided a holding device for holding an object. a plate having a first surface on which the object is placed and a second surface opposite to the first surface, a plate-shaped portion formed in a shape of a plate-shaped member; and a support member arranged on the second surface side of the plate-shaped portion and supporting the plate-shaped portion; A base portion having a cooling function and formed in a plate shape, and a cooling device disposed between the plate-shaped portion and the base portion and a joint portion that joins the plate-shaped portion and the base portion, and the thermal resistance of the joint portion is , 1.1 × 10 at -60°C -3 (m 2 K / W) or less.

[0008] With this type of holding device, the thermal resistance of the junction is 1.1 x 10 at -60°C. -3 (m 2 K / W) or less, and the thermal resistance is small, so for example, the plate-shaped part of the holding device becomes hot and the When the base part is used at an extremely low temperature of about -60°C, the plate part can be cooled rapidly. Therefore, the cooling rate of the surface on which the object is placed can be improved.

[0009] (2) In the holding device of the above embodiment, the joint has a thermal conductivity of λ1 at −60° C. When the thermal conductivity at 25°C is λ2, λ1 / λ2 is 1.18 or less. When the thermal resistance at -60℃ is θ1 and the thermal resistance at 25℃ is θ2, then, 1 / θ2 is 0.85 or more. With this structure, the change in thermal conductivity due to the temperature change of the joint is small, so the temperature of the plate-shaped part The uniformity of distribution can be improved.

[0010] (3) In the holding device of the above embodiment, the thermal resistance of the joint at 25°C is 1.2×1 0 -3 (m 2 With such a configuration, the operating temperature of the holding device may be less than 100 K / W. Even if the temperature is room temperature (25°C), the joint has good thermal conductivity, so the plate can be cooled quickly. It can be dismissed.

[0011] (4) In the above-mentioned holding device, the joint has a thermal conductivity of 25°C and -60°C. The electrical conductivity may be 0.7 (W / mK) or more. With this configuration, For example, sufficient thermal conductivity can be obtained even at low temperatures (for example, -60°C) or at room temperature.

[0012] (5) In the holding device of the above embodiment, the joint portion contains aluminum nitride (AlN). In this way, the flexibility and stress relaxation performance are good, and the thermal conductivity is good. It is possible to provide a suitable joint.

[0013] (6) In the above-mentioned holding device, the strain amount at the maximum shear stress of the joint is 0.5 In this way, the flexibility of the joint and the stress relaxation Therefore, when a shear force is applied to the joint, This can reduce damage to the joints.

[0014] (7) In the holding device of the above embodiment, a hole penetrating the base portion and an inner wall of the hole an insulating portion covering the plate-shaped portion; an end surface of the insulating portion facing the second surface of the plate-shaped portion; and a hole joint portion that joins the hole joint portion to the material constituting the joint portion. The second portion may be made of the same material and may be thinner than the joint portion. In the holding device, the base portion has a hole portion penetrating therethrough, and therefore the plate portion has a corresponding hole portion. Therefore, with this configuration, the hole joint has good thermal conductivity. Since the portion of the plate-shaped part corresponding to the hole can dissipate heat through the hole, the temperature of the plate-shaped part can be Non-uniformity can be suppressed.

[0015] The present disclosure may be realized in various forms other than those described above. For example, a semiconductor manufacturing device including a holding device The present invention can be realized in the form of a manufacturing device, a manufacturing method for a holding device, a method for forming a joint, etc. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is an explanatory diagram illustrating a schematic configuration of an electrostatic chuck according to a first embodiment. [Diagram 2] FIG. 2 is an explanatory diagram illustrating a cross-sectional configuration of the electrostatic chuck. [Diagram 3] FIG. 11 is an explanatory diagram illustrating the evaluation results of each sample. [Figure 4] FIG. 2 is an explanatory diagram showing the composition of each sample. [Diagram 5] FIG. 1 shows the particle size distribution of 10 μm alumina. [Figure 6] FIG. 1 shows an SEM image and particle size distribution of 15 μm aluminum nitride. [Figure 7] FIG. 1 shows an SEM image and particle size distribution of aluminum nitride 5 μm. [Figure 8] FIG. 1 shows an SEM image and particle size distribution of 2 μm aluminum nitride. [Figure 9] FIG. 4 is an explanatory diagram showing the temperature dependence of thermal conductivity of each sample. [Figure 10] FIG. 4 is an explanatory diagram showing the temperature dependence of thermal resistance of each sample. [Figure 11] FIG. 4 is an explanatory diagram showing the temperature dependence of thermal resistance of each sample. [Figure 12] FIG. 2 is an explanatory diagram illustrating a method for calculating a maximum shear stress and an amount of strain. [Figure 13] FIG. 4 is a diagram showing the composition and thermal conductivity of a sample using a first silicone resin. [Figure 14] FIG. 4 is a diagram showing the composition and thermal conductivity of a sample using a first silicone resin. [Figure 15] 1 shows a ternary diagram of the thermal conductivity of a sample using a first silicone resin. [Figure 16]FIG. 13 is a diagram showing the composition and thermal conductivity of a sample using a second silicone resin. [Figure 17] FIG. 13 is a diagram showing the composition and thermal conductivity of a sample using a second silicone resin. [Figure 18] FIG. 13 shows a ternary diagram of the thermal conductivity of a sample using a second silicone resin. [Figure 19] FIG. 11 is a cross-sectional view illustrating a schematic configuration of an electrostatic chuck according to a second embodiment. [Figure 20] FIG. 20 is an enlarged view of a portion X in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] A. First embodiment: (A-1) Overall structure of electrostatic chuck: FIG. 1 is an explanatory diagram that roughly illustrates the configuration of an electrostatic chuck 10 according to the first embodiment. FIG. 2 is an explanatory diagram showing a schematic cross-sectional configuration of the electrostatic chuck 10. The block 10 is shown partially cut away. The intersecting X, Y and Z axes are shown. For convenience, the positive direction of the Z axis is referred to as the upward direction in this specification. The negative direction of the Z axis is referred to as the downward direction, but the electrostatic chuck 10 is actually oriented in this manner. The X-axis, Y-axis, and Z-axis shown in each figure are in the same direction. Note that the above figures show the layout of each part only diagrammatically, and the dimensional ratio of each part is not accurately expressed. It is not an exact representation.

[0018] The electrostatic chuck 10 is a device that attracts and holds an object by electrostatic attraction. Used to hold the target wafer W (Figure 2) in the vacuum chamber of a semiconductor manufacturing device. The electrostatic chuck 10 includes a plate-shaped portion 20, a base portion 30, and a joint portion 40. These are the plate-shaped portion 20, the joint portion 40, the base portion 3, and the like, in the -Z-axis direction (vertically downward). The electrostatic chuck 10 in this embodiment is also called a "holding device." Oink.

[0019] The plate-shaped portion 20 has a first surface 24 on which an object is placed and a second surface 25 on the opposite side of the first surface 24. 26, and is a substantially circular plate-shaped member made of ceramic (e.g., aluminum oxide or nitride). In the present specification, the specific component is defined as "main "A component" or "A material that mainly forms the component" means that the content of the specific component is 50% or more. The diameter of the plate-shaped portion 20 is, for example, 50 mm to 500 mm. The thickness of the plate-like portion 20 is, for example, about 200 mm to 350 mm. For example, it may be about 1 mm to 10 mm. Alternatively, the ceramic insulating layer 11 may be formed mainly from a material other than ceramic, such as a resin such as polyimide.

[0020] As shown in Fig. 2, an adsorption electrode 22 is disposed inside the plate-shaped portion 20. The electrode 22 is made of a conductive material such as tungsten or molybdenum. When a voltage is applied to the attachment electrode 22 from a power source (not shown), an electrostatic force is generated. The wafer W is attracted and fixed to the first surface 24 of the plate-shaped portion 20 by electrostatic attraction. The plate-shaped portion 20 may be of a bipolar type or a monopolar type. The heater is made of a resistance heating element made of a material (e.g., tungsten or molybdenum), A heater electrode (not shown) is provided to heat the wafer W fixed by suction to the first surface 24. Good too.

[0021] The base portion 30 is disposed on the second surface 26 side of the plate-shaped portion 20, supports the plate-shaped portion 20, and The base portion 30 is a plate-like member formed in a substantially circular shape. At least one of magnesium, molybdenum, titanium, tungsten, and nickel The metals molybdenum, titanium, and tungsten can be used as the above-mentioned metals. Among metals, the thermal expansion coefficient is relatively small, so at least one of these metals is used. In the case where the base portion 30 is formed by the above, the difference in the thermal expansion coefficient between the base portion 30 and the plate-shaped portion 20 is suppressed. In this specification, the term "thermal expansion coefficient" means "linear expansion coefficient". In addition, since magnesium has a relatively small Young's modulus, In the case where the base portion 30 is formed, it is desirable to reduce the thermal stress occurring in the base portion 30. In addition, aluminum has a relatively high thermal conductivity, is easy to process, and is low in cost. Therefore, when the base portion 30 is made of aluminum, The cooling efficiency of the plate-shaped portion 20 and the wafer W can be improved, and the manufacturing cost of the electrostatic chuck 10 can be reduced. This is desirable because it is possible to reduce the manufacturing cost while increasing the cooling efficiency of the base portion 30. From the viewpoint of suppressing the occurrence of heat, it is desirable that the metal content in the base portion 30 is high. It is preferable that the main component of 30 is a metal. For example, 90% of the material is made of aluminum, which is highly versatile. % by mass or more (for example, aluminum alloys such as A6061 and A5052) However, the base portion 30 may be made of a material other than metal, such as ceramic. The diameter of the base portion 30 is, for example, about 220 mm to 550 mm. The thickness of the base portion 30 is, for example, 220 mm to 350 mm. It should be about 0mm to 40mm.

[0022] A plurality of refrigerant flow paths 32 are formed inside the base portion 30 along the XY plane. By passing a coolant such as a fluorine-based inert liquid, water, or liquid nitrogen through the coolant flow passage 32, The base portion 30 is cooled. Then, the base portion 30 and the plate-shaped portion 20 are joined together via the joint portion 40. The plate-shaped portion 20 is cooled by heat transfer between the first surface 24 of the plate-shaped portion 20. In this way, the temperature of the wafer W is controlled. In addition to the configuration having the medium flow passage 32, the base portion 30 may be cooled from the outside of the base portion 30. In this way, the base portion 30 may have a cooling function.

[0023] The joint portion 40 is disposed between the plate-shaped portion 20 and the base portion 30. The joint 40 includes an adhesive formed of a resin material. The adhesive 0 further adjusts the properties of the joint 40 and the properties of the paste for forming the joint 40. In other words, the joint 40 may contain various fillers (inorganic fillers) for the purpose of The joint 40 may be made of a composite material containing an adhesive and an inorganic filler. The joint 40 may not contain an inorganic filler as long as it satisfies the properties described below. From the viewpoint of reducing the thermal resistance of the joint 40, the thickness of the joint 40 is, for example, 1.00 mm or less. It is preferable that the thickness is 0.60 mm or less, more preferable that the thickness is 0.50 mm or less, and 0.3 The thickness of the joint 40 is preferably 5 mm or less. From the viewpoint of ensuring strength, it is sufficient to set the thickness to 0.05 mm or more. The joint 40 will be described in detail later. State.

[0024] The electrostatic chuck 10 further includes a plurality of gas supply paths 50. 50 is provided penetrating the plate-shaped portion 20, the joint portion 40, and the base portion 30 in the Z direction. The gas supply is opened at a gas outlet port 52 formed in the first surface 24 (see FIG. 1). The supply path 50 is supplied with an inert gas, such as helium gas, from a gas supply device (not shown). Then, an inert gas is supplied from the gas discharge port 52 to the space between the first surface 24 and the wafer W. This increases the heat transfer between the plate-shaped portion 20 and the wafer W, and distributes the temperature of the wafer W. The controllability of the fabric is further improved. Note that the gas supply path 50 is not essential, and the electrostatic chuck 1 0, the gas supply path 50 may not be provided.

[0025] (A-2) Joint configuration: The thermal resistance of the joint 40 of the electrostatic chuck 10 of this embodiment is 1.1 at −60° C. ×10 -3 (m 2 The thermal resistance of the junction 40 is R(m 2 K / W), joint 40 If the thickness of the joint 40 is t (m) and the thermal conductivity of the joint 40 is λ (W / mK), the thermal resistance of the joint 40 is The resistance R is calculated by the following formula (1).

[0026] R(m 2 K / W) = t(m) ÷ λ(W / mK) … (1)

[0027] In an environment where the electrostatic chuck 10 is exposed to strong plasma energy, When the device is used in an environment where high power is input to the device, the first surface 24 of the plate-shaped portion 20 is likely to become hot. In the case where the first surface 24 of the plate-shaped portion 20 is used under conditions where the temperature becomes, for example, 120° C. In order to cool the base unit 20, the temperature of the coolant supplied to the base unit 30 is set to, for example, about -60°C. When the base portion 30 becomes cold, the joint portion 40 also becomes cold. By setting the thermal resistance of the junction 40 at .degree. C. to the above value, the temperature of the base portion 30 can be extremely low. When the temperature is lowered to a temperature (for example, −60° C.), the base portion 30 and the plate-shaped portion 20 are Heat transfer between the plate-shaped portion 20 and the base portion 30, that is, heat transfer from the plate-shaped portion 20 to the base portion 30, is facilitated, and electrostatic This can improve the cooling efficiency of the chuck 10. As described above, the joint 40 is made of resin. The adhesive generally has a lower thermal conductivity as the temperature increases. That is, when the thickness of the joint 40 is constant, the thermal resistance increases as the temperature increases. If the thermal resistance of the junction 40 at −60° C. is set to the above value, Even if the temperature of the cooling fan becomes higher than -60℃, sufficient cooling performance can be obtained. This can improve the cooling rate of the surface (first surface 24) on which the object is placed.

[0028] The thermal conductivity of the joint 40 is not particularly limited, but the thermal conductivity at −60° C. is defined as λ1. When the thermal conductivity at 25°C is λ2, it is preferable that λ1 / λ2 is 1.18 or less. Here, 25° C. is the room temperature (normal temperature) when the electrostatic chuck 10 is used. As shown above, the thermal conductivity of the adhesive generally decreases as the temperature increases. When the thermal conductivity is set as described above, the change in thermal conductivity of the joint 40 due to the temperature change is small. If the change in thermal conductivity due to the temperature change of 40 is large, the low temperature part will be cooled more and the high Since the hot portion cools slowly, there is a risk that the temperature difference between the top, bottom, and surface of the joint 40 will become large. In contrast, when the thermal conductivity of the joint 40 is set as described above, the thermal conductivity of the joint 40 increases with the temperature change. Since the change in thermal conductivity is small, the temperature difference between the upper and lower parts of the joint 40 and within the plane can be suppressed. In other words, the uniformity of the temperature distribution in the plate-like portion 20 can be improved. , λ1 / λ2 is usually 1.00 or more.

[0029] Regarding the thermal resistance of the junction 40, the thermal resistance at -60°C is θ1, and the thermal resistance at 25°C is θ2. When the resistance is θ2, it is preferable that θ1 / θ2 is 0.85 or more. Since the change in thermal resistance due to the temperature change of the joint 40 is small, In other words, the temperature difference in the plane can be suppressed. It is possible to improve the angle. Note that θ1 / θ2 is usually 1.00 or less.

[0030] The thermal resistance of the joint 40 at 25° C. is not particularly limited, but is preferably 1.2×10 -3 (m 2 K / In this way, the operating temperature of the electrostatic chuck 10 is preferably equal to or less than room temperature (25° C.). Even in this case, since the joint 40 has good thermal conductivity, the plate-shaped portion 20 can be cooled rapidly. This can be done.

[0031] The strain amount at the maximum shear stress of the joint 40 is not particularly limited, but is preferably 0.5 mm or more. It is preferable that the thickness is 1.0 mm or more, and more preferable that the thickness is 1.1 mm or more. The strain at the joint 40 under maximum shear stress is usually 5.0 mm or less. The strain amount at maximum shear stress is an index showing the flexibility and stress relaxation performance of the joint 40. This is the value at which the shear stress generated at the joint 40 when a shear force is applied to the joint 40 is the minimum. When the shear stress becomes large, i.e., when the maximum shear stress occurs at the joint 40, This refers to the magnitude of the strain (displacement in the direction of the shear force) that occurs. The amount of strain is large at maximum shear stress. The greater the value, the greater the flexibility of the joint 40. The specific measurement method using a tensile tester for this purpose will be described in detail later. If the strain amount at maximum shear stress of 0 is set to the above value, the flexibility and stress relaxation of the joint 40 can be improved. Therefore, when a shear force is applied to the joint 40, the performance can be sufficiently ensured. This can suppress damage to the joint 40 during the welding.

[0032] The lower limit of the thermal resistance of the joint 40 is, for example, 0.6×10 -4 (m 2 K / W) In order to suppress the thermal resistance of the joint 40, the inorganic filler is added as described above. One possible method is to appropriately select the material to be used and increase the content of inorganic filler. However, if the content of the inorganic filler is excessively increased, the flexibility of the joint 40 is impaired. As a result, it may become difficult to sufficiently secure the magnitude of the strain amount at the maximum shear stress of the joint 40, which will be described later. In order to reduce the thermal resistance of the joint 40, it is possible to make the joint 40 thinner. However, if the joint 40 is made too thin, the strength of the joint 40 decreases. At the same time, it becomes difficult to ensure the flexibility of the joint 40, and the strain amount at the maximum shear stress is reduced to a desired value. Therefore, the thermal resistance of the junction 40 may be set to the above range. 0.6×10 -4 (m 2 It is desirable to set the temperature at or above 100 K / W.

[0033] The amount of strain at the maximum shear stress of the joint 40 is determined by the adhesive (resin) contained in the joint 40. For example, the maximum shear stress can be changed depending on the type of resin that constitutes the joint 40. In addition to being able to change the amount of strain when force is applied, even if the same type of resin is used, the resin is a polymer material. By controlling the distance between the crosslinking points in the resin, the strain amount at the maximum shear stress of the joint 40 can be Specifically, the content of the functional group that serves as the crosslinking point in the resin (functional group equivalent) By reducing the crosslinking point distance, the flexibility of the resin is improved, and the maximum shear strength is reduced. The amount of strain under stress can be increased. In addition, the content of reactive functional groups in the resin is Even in the same case, the distance between crosslinks may vary depending on the curing conditions such as the resin curing temperature and curing time. That is, when the curing temperature is increased or the curing time is extended, In this case, the resin hardens further, the crosslink density increases, and the distance between crosslinks becomes shorter. become.

[0034] In addition, the amount of strain at the maximum shear stress of the joint 40 increases as the thickness of the joint 40 increases. So it can be made larger.

[0035] In addition, the greater the content of the inorganic filler in the joint 40, the greater the maximum shear strength of the joint 40. The strain under tensile stress tends to be smaller. This is because the content of inorganic filler is higher. The degree to which the inorganic filler binds the surrounding resin (resin composition) increases, and the flexibility of the joint 40 increases. This is believed to be because the flexibility decreases, making the joint 40 less susceptible to distortion.

[0036] The adhesive that constitutes the joint 40 may be, for example, a silicone resin, an acrylic resin, or the like. In particular, silicone resin has relatively high heat resistance and Among these resins, silicone resin has a relatively high elastic modulus. Since the temperature is low, the function of mitigating thermal stress occurring at the joint 40 is high, and the heat resistance temperature is relatively high. High, therefore desirable.

[0037] Inorganic fillers include ceramics, metal oxides, metals, or other inorganic compounds. Various granular or powdery substances made of inorganic materials can be used. Examples of inorganic fillers include aluminum nitride (AlN) and aluminum oxide (Al). Lumina: Al 2 O 3 ), zirconium oxide (zirconia: ZrO 2 ), yttrium oxide ( Yttria:Y 2 O 3 ), yttrium fluoride (YF 3 ), silicon carbide (SiC), nitride Iron (Si 3 N 4 ), silicon dioxide (silica: SiO 2 ), iron oxide, barium sulfate, calcium carbonate The inorganic filler may be made of the above-mentioned inorganic materials. In addition, since the thermal conductivity of the inorganic filler is higher than that of the resin used as the adhesive, the inorganic filler is added to the joint 40. This can increase the thermal conductivity at the joint 40. From the viewpoint of making it easier to suppress the thermal resistance of the joint 40, the material constituting the inorganic filler is As the material, aluminum nitride, aluminum oxide, and silicon carbide are preferable. Aluminum and aluminum oxide are particularly preferred.

[0038] The bonding portion 40 may further include a catalyst for promoting the curing reaction, or a bonding agent for promoting curing and adhesion. Silane coupling agents for imparting heat, crosslinking agents, and reaction agents for adjusting the curing speed of adhesives The joint 40 may contain a reaction inhibitor, a viscosity adjuster, or the like. Various conventional catalysts can be used, such as platinum catalysts, rhodium catalysts, and titanium catalysts. Among them, platinum catalyst, which has high reactivity, is used. The silane coupling agent contained in the bonding portion 40 is not particularly limited, and examples thereof include , as organic reactive groups, vinyl groups, epoxy groups, methacryl groups, amino groups, mercapto groups, Among the conventionally known silane coupling agents, those having either an isocyanate group or Alternatively, instead of the silane coupling agent, a titanate coupling agent may be used. Alternatively, a coupling agent based on ethoxylated or aluminate based may be used. The crosslinking agent is an organohydride having at least three hydrosilyl groups in one molecule. More specifically, for example, polymethyl halides polysiloxane can be used. Hydrogensiloxane and poly(dimethylsiloxane-methylhydrogensiloxane) At least one of the above can be used.

[0039] As the reaction inhibitor contained in the joint 40, various conventionally known reaction inhibitors can be used. For example, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclopentadiene Lasiloxane, 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, Tria The viscosity modifier contained in the joint 40 may be, for example, butyl isocyanurate. Various viscosity modifiers known in the art can be used, such as fumed silica, fumed silica, etc. Silica, colloidal silica, fumed alumina, colloidal alumina, etc. The above-mentioned catalysts, silane coupling agents, crosslinking agents, reaction inhibitors, and The type and amount of viscosity modifier, etc., depends on, for example, the type of resin constituting the joint 40. An appropriate selection may be made depending on the situation.

[0040] According to formula (1), the thermal resistance of the joint 40 is reduced by reducing the thickness of the joint 40. For example, by making the thickness of the joint 40 0.5 mm or less, Thermal resistance at -60°C is 1.1×10 -3 (m 2 It is now easier to keep it below 100K / W. In addition, by increasing the thermal conductivity of the joint 40 to, for example, 0.7 W / mK or more, the joint Even if the thickness of the joint 40 is made larger than 0.5 mm, the thermal resistance of the joint 40 at −60° C. 1.1×10 -3 (m 2 It is relatively easy to keep the thermal conductivity of the joint 40 below 100 K / W. To increase the thermal conductivity, for example, inorganic fillers made of materials with higher thermal conductivity can be used, as described below. or by increasing the content of inorganic filler.

[0041] The thermal resistance of the joint 40 depends on, for example, the material of the inorganic filler contained in the joint 40 and the joint The amount of inorganic filler in the joint 40 and the type of resin contained in the joint 40 may be changed. By using inorganic fillers made of materials with higher thermal conductivity, By increasing the content of inorganic filler, it is possible to obtain a resin with higher thermal conductivity. By using grease, the thermal conductivity of the joint 40 is increased, and the thermal resistance of the joint 40 is reduced. It is possible.

[0042] Furthermore, the thermal resistance of the joint 40 depends on the shape of the particles of the inorganic filler contained in the joint 40. can be changed.

[0043] The inorganic filler may be formed from a homogeneous material, or may be formed from a material that constitutes the particle body of the inorganic filler. A coating layer made of a material different from the material of the coating layer may be provided on the surface. By selecting the appropriate material, it is possible to improve the water resistance of the inorganic filler and improve the compatibility between the inorganic filler and the resin. It is possible to improve the flexibility of the joint 40. For example, When aluminum nitride powder is used as the inorganic filler, the aluminum nitride particles constituting the inorganic filler On the surface of 2 ), aluminum oxide (Al 2 O 3 ), or phosphoric acid Aluminum (AlPO 4 ) may be provided as a coating layer.

[0044] In the electrostatic chuck 10, the base portion 30 generally has a higher thermal expansion coefficient than the plate-shaped portion 20. It has high elasticity and expands and contracts greatly with temperature changes. In some cases, the degree of thermal expansion of the plate-shaped portion 20 may be greater than the degree of thermal expansion of the plate-shaped portion 20. In this way, since the degree of expansion and contraction differs between the plate-like portion 20 and the base portion 30, In the joint 40, a shear force in the X-axis direction is applied, generating a shear stress. As described above, by increasing the magnitude of the strain amount at the maximum shear stress of the joint 40, Therefore, even if a large shear force is applied to the joint 40, the shear force generated at the joint 40 is small. Stress can be reduced and damage to the joint 40 can be suppressed.

[0045] As described above, according to the electrostatic chuck 10 of the present embodiment, The thermal resistance of the junction 40 is 1.1×10 at -60°C. -3 (m 2 K / W) or less. Therefore, when the heat input to the plate-shaped portion 20 is larger and the base portion 30 is very low, Even when the electrostatic chuck 10 is heated to a low temperature (e.g., −60° C.), the cooling performance of the electrostatic chuck 10 is improved. As a result, an excessive temperature rise in the plate-shaped portion 20 is suppressed, and the heat generated by the heat generated by the plate-shaped portion 20 is prevented. The deterioration of the processing accuracy of the wafer is suppressed, and the contact between the plate-shaped portion 20 and the base portion 30 is prevented by the temperature difference. The shear stress occurring at the joint 40 can be suppressed.

[0046] In addition, for the joint 40, the thermal conductivity at -60°C is λ1, and the thermal conductivity at 25°C is λ2. When the conductivity is λ2, λ1 / λ2 must be 1.18 or less, or the thermal resistance at -60℃ When θ1 is the thermal resistance at 25°C and θ2 is the thermal resistance at 25°C, θ1 / θ2 must be 0.85 or more. This can reduce the change in thermal conductivity of the joint 40 due to the change in temperature. The temperature difference above, below and within the surface of 40 can be suppressed.

[0047] In addition, the thermal resistance of the junction 40 at 25°C is 1.2×10 -3 (m 2 K / W or less As a result, even when the electrostatic chuck 10 is used at room temperature (25° C.), the bonding portion 40 has good thermal conductivity. Because it has conductivity, the plate-shaped portion 20 can be cooled rapidly.

[0048] In addition, the larger the strain amount at the maximum shear stress of the joint 40 is, the greater the stress relaxation of the joint 40 is. In order to improve performance, the strain at maximum shear stress of the joint 40 is set to 0.5 mm or more. Even if shear stress occurs in the joint 40, the joint Damage to the joint 40 can be suppressed.

[0049] Such effects are particularly prevalent when the electrostatic chuck 10 is exposed to higher power plasmas. This is particularly noticeable when the heat input to the plate-shaped portion is large. Even if a heater electrode for heating is not provided, the electrostatic charge can be generated with high plasma power. When the chuck 10 is used, the temperature difference between the mounting surface of the plate-shaped portion 20 and the base portion 30 becomes large. Therefore, the effect of this embodiment is remarkable. EXAMPLES

[0050] The holding device of the present disclosure will be described below based on an embodiment. The joints were then subjected to a test with different modulus, thermal resistance, and strain at maximum shear stress. As corresponding samples, sheet-shaped samples 1 to 11 were prepared. The electrostatic chuck-shaped samples each having a joint with the same composition as that of each of the sheet-shaped samples 1 to 11 were In the following, the electrostatic chuck sample was also fabricated with the same composition as the joint. It is called by the same sample number as the sheet-shaped sample.

[0051] Figure 3 shows the thickness of the joint, thermal conductivity (-60℃, 25℃), and thermal conductivity ratio ( -60℃ / 25℃), thermal resistance, thermal resistance ratio (-60℃ / 25℃), strain at maximum shear stress The results of the evaluation of the temperature distribution and the temperature drop rate of the plate part of the electrostatic chuck are shown together with the weight value. FIG. 4 is an explanatory diagram showing the composition of each sample. FIG. FIG. 6 shows the particle size distribution of 10 μm alumina used in the sample. FIG. 7 is a diagram showing an SEM image and particle size distribution of 15 μm aluminum nitride. This shows an SEM image and particle size distribution of 5 μm aluminum nitride used in the sample. Figure 8 shows an SEM image and particle size distribution of 2 μm aluminum nitride used in the sample. FIG. 9 is an explanatory diagram showing the temperature dependence of the thermal conductivity of each sample. 10 and 11 are diagrams illustrating the temperature dependence of the thermal resistance of each sample. 1 shows the results for samples with a thickness of 0.5 mm (samples 1, 3, 4, 6, 8, and 10). Figure 11 shows the results for samples 1, 3, 4, and 6, enlarged (the maximum value on the vertical axis is smaller than that in Figure 10). The figures are shown in simplified form.

[0052] <Preparation of each sample> [Preparation of sheet-like samples] In each sample, silicone resin was used as the adhesive. The adhesive material (resin material) is polydimethylsiloxane and contains 5 mol% phenyl groups. Specifically, samples 1 to 3 were made of either phenanthroline or polydimethylsiloxane. Samples 4 to 11 were made of polydimethylsiloxane containing 5 mol% of silyl groups. As shown in Figure 4, Samples 1 and 2, Samples 4 and 5, and Sample Samples 6 and 7, 8 and 9, and 10 and 11 have the same composition, as shown in Figure 3. As shown, one is 0.5 mm thick and the other is 1 mm thick. The composition is as shown in FIG.

[0053] Among the fillers shown in FIG. 4, "alumina 10 μm" is a filler having an average particle size of 10 μm. Alumina particles with a BET specific surface area of ​​1.3 m 2 / g. The particle size distribution is shown in Figure 5. The average particle size was determined by the following method using the particle size distribution. The shape of the 10 μm Mina is almost spherical (Figure 4). When the radius of the circumscribed circle is R1 and the radius of the circumscribed circle is R2, the average value of "R2 / R1" A sphere is considered to be a perfect sphere when its radius is close to 1.0 (for example, less than 1.05). The average particle size can be measured using a known particle size distribution measuring device. After dispersing the particles in water, the cumulative frequency is measured using a Microtrac MT3000II, for example. The diameter at which the particle size reaches 50% is taken as the average particle size. The method for determining the average particle size is as follows for aluminum nitride: The same is true.

[0054] "Aluminum nitride 15μm" is aluminum nitride particles with an average particle size of 15μm. The BET specific surface area is 0.9m 2 / g. The particle size distribution is shown in FIG. "Aluminum nitride 5μm" is aluminum nitride particles with an average particle size of 5μm, and is The specific surface area is 1.3m 2 The particle size distribution is shown in Figure 7. "Aluminum 2μm" is an aluminum nitride particle with an average particle size of 2μm, and has a BET specific surface area of The volume is 2.8m 2 The particle size distribution is shown in Figure 8. The shape is angular. Here, the "angular" shape is the shape of the SEM (scanning electron microscope) shown in Figs. As shown in the image, the particles are irregular and angular, and are not cuboid, spherical, rod-like, or plate-like in shape. If the particle shape of the filler is not a perfect sphere but has corners, the number of contact points between the particles increases, This makes it easier for a heat conduction path to be formed within the joint 40, and reduces the thermal resistance of the joint 40.

[0055] The sheet-like sample was prepared as follows. Filler and silicone resin were mixed to create a paste-like adhesive. The mixing may be performed by any of a variety of methods, including mixing with a known agitating blade, a three-roll mixer, a kneader, a rotating / revolving mixer, a press, etc. The prepared paste-like adhesive is mixed with a known The coating device spreads the material on a release film and hardens it to produce a sheet-like sump. Coating devices include, for example, roll coaters, bar coaters, die coaters, etc. A machine such as a knife coater or a press machine can be used. Polyethylene terephthalate (PET) film can be used to improve release properties. PET film coated with a release agent may be used. To obtain a thick or block-shaped cured product, the adhesive is placed in a container of a specified size. After pouring the liquid into the container, it may be allowed to harden. If necessary, heating may be performed for hardening.

[0056] [Preparation of electrostatic chuck-type sample] The electrostatic chucks of Samples 1 to 12 are all the electrostatic chucks of the first embodiment shown in FIG. The sample in the form of the electrostatic chuck 10 is the semi-hard chuck described above. The cured adhesive paste is placed between the plate-shaped portion 20 and the base portion 30, and then the adhesive paste is The plate-shaped portion 20 was made of aluminum oxide. The plate-shaped portion (coefficient of thermal expansion: 7 ppm / K) is made of aluminum. The base portion 20 is made of aluminum (coefficient of thermal expansion: 23 ppm / K). The diameter of the joint was 350 mm.

[0057] <Evaluation method> Thermal conductivity Thermal conductivity was measured using a known thermal conductivity meter (Agne thermal conductivity The measurement was performed using a thermal conductivity measuring device (ARC-TC-1000) by the hot wire method (probe method). Instead of a block-shaped sample, the test was performed on a joint mounted on an electrostatic chuck. When measuring the thermal conductivity, the plate-shaped part of the electrostatic chuck is scraped off with a surface grinder, etc., and the joint After exposing the wire, the joint can be peeled off with a knife or similar tool and the thermal conductivity can be measured. .

[0058] ·Thermal resistance The thermal resistance R is calculated as follows using the measured thermal conductivity of each sample as described above. In equation (1), t is the thickness of the joint, λ is the thermal Conductivity, i.e., the thermal conductivity of each sample, measured as described above.

[0059] R(m 2 K / W) = t(m) ÷ λ(W / mK) … (1)

[0060] -Strain at maximum shear stress The strain at maximum shear stress was measured using a known tensile testing machine (Shimadzu Autograph AGS- The measurements were performed using a tensile tester (5kNX).

[0061] FIG. 12 is an explanatory diagram showing a schematic diagram of a method for calculating the maximum shear stress and the amount of strain. 12(A) shows the front view of the tensile test, and Figs. 12(B) and 12(C) show 12(A) and 12(B) show the state at the start of the test. FIG. 12(C) shows the state after the start of the test. ,The semi-cured adhesive sheet of each sample was cut into two pieces of 25 mm wide x 100 mm long x 1 mm thick. The 25mm x 12.5mm part of the aluminum plate 80 is 12.5mm from the edge of the plate. The two aluminum plates 80 can be pulled in opposite directions. After bonding them in the direction indicated, the semi-cured adhesive sheet was cured to produce the film. The thickness t of the test piece 70 at the start of the test was set to the thickness of the joint shown in Figs. The two aluminum plates 80 are attached to a tensile test fixture so that a shear force is applied to the test piece. The two aluminum plates were held in place by a tensile tester and moved relative to each other. The specimen was moved in one direction parallel to the adherend at a pulling speed of 2 mm / min. The strain amount δ at the specimen was measured (see Fig. 12(C)). The tensile tester and the fixture had sufficient rigidity. The highest strain was used, and the travel distance of the tool of the tensile tester was taken as the strain amount δ. The direction of relative movement of the two aluminum plates is indicated by the white arrows. Calculate the shear stress by dividing by the bond area of ​​the previous test piece (25 mm x 12.5 mm). Such relative movement of the two aluminum plates was continued until the test piece 70 broke. The shear stress at which the shear stress reaches its maximum is called the maximum shear stress (unit: MPa). The strain at maximum shear stress (unit: mm) was measured in the tensile test shown in Figure 12. The strain amount δ was determined when the shear stress reached its maximum. When measuring the strain at maximum shear stress of a joint that is connected to a concrete, for example, First, the joint is cut into the adherends (the plate-shaped part and the base) by a processing method such as laser cutting. The shape of the test piece to be cut out can be held by the jig of the tensile testing machine. In addition, the two joined adherends are pulled in opposite directions as shown in FIG. Before the tensile test, the joints of the cut specimens were The area of ​​the joint and the thickness of the joint are measured. Then, the tensile test is performed in the same manner as described above. Then, the strain at the maximum shear stress is measured.

[0062] Temperature distribution in plate-shaped part The temperature distribution of the plate-shaped portion of each of the electrostatic chuck samples 1 to 11 was evaluated. was set so that the average surface temperature of the plate-shaped part of each sample was constant over time at about 100°C. The plate-shaped part was heated, and at the same time, a coolant at -60°C was supplied to the coolant passage of the base part to cool it. When the temperature difference between the maximum and minimum surface temperatures of the plate-shaped part is less than 2°C, it is marked as "◎", and when it is 2°C or more but less than 5°C, it is marked as "◎". The surface temperature of the plate-shaped part and its change over time were evaluated as follows: The plate-shaped part can be heated by irradiating it with plasma. In addition, if a heater electrode is provided on the plate-shaped portion, heating can also be achieved by passing electricity through the heater electrode. This may be used in combination with heating by plasma irradiation.

[0063] -Temperature drop rate of plate part For each of the electrostatic chuck samples 1 to 11, the same evaluation method for the temperature distribution of the plate-shaped portion as described above was used. The plate is heated so that the average surface temperature of the plate is constant over time at about 100°C. At the same time, a -60°C coolant is supplied to the coolant passage of the base to cool it, and then the plate-shaped part is heated. The heating of the plate-shaped part was stopped, and the cooling of the base part was continued. The change in the average surface temperature over time was measured. It took 10 minutes for the average temperature of the plate to cool to below 0°C. The time required was measured, and a score of "Good" was given if it took 15 seconds or less, and a score of "Poor" if it took more than 15 seconds. Ta.

[0064] Samples 1 to 7 meet the following requirement [1]. [1] The thermal resistance of the junction is 1.1 x 10 at -60°C. -3 (m 2 K / W) or less.

[0065] Samples 1 to 3 meet the above requirement (1) as well as the following requirements (2) and (3). It is. [2] The thermal conductivity of the joint is λ1 at -60°C and λ2 at 25°C. When this is set, λ1 / λ2 is 1.18 or less. [3] The thermal resistance of the junction is θ1 at -60°C and θ2 at 25°C. When the angle is θ1 / θ2, the ratio is 0.85 or more.

[0066] Samples 1 to 6 meet the above requirement [1] as well as the following requirement [4]. do. [4] The thermal resistance of the junction at 25°C is 1.2×10 -3 (m 2 K / W) or less.

[0067] Samples 1 to 7 further satisfy the following requirement [5]. [5] The joint has a thermal conductivity of 0.7 (W / mK) or more at 25°C and -60°C. do.

[0068] Samples 1, 2, 4, and 5 further meet the requirement of [6] below. [6] The joint contains aluminum nitride (AlN).

[0069] Samples 1 to 7 further satisfy the following requirement [7]. [7] The strain at maximum shear stress of the joint is 0.5 mm or more.

[0070] Thus, samples 8 to 11 meet at least the above requirement (1). The temperature distribution and temperature drop rate of the plate-shaped part were rated as "X" (Figure 3).

[0071] As shown in Figure 3, Sample 1 7 In the test, the temperature distribution and the temperature drop rate were evaluated as "good" or "good". In other words, by satisfying the above requirement [1], it can be said that the transfer of heat from the plate-shaped part to the base part was improved.

[0072] Furthermore, Samples 1 to 3 satisfy the above requirements [2] and [3], and as shown in Figs. As shown in Fig. 1, there is no temperature range where the thermal conductivity and thermal resistance change suddenly. Compared to samples 8 to 11, this has a smaller thermal resistance and can cool the plate-shaped part rapidly. The thermal conductivity and thermal resistance of the material change rapidly in the range of -20℃ to -40℃ (Fig. 9, Fig. 1 1) This allows the lower temperature parts of the plate to be cooled more, improving temperature uniformity. In contrast, as described above, samples 1 to 3 have high thermal conductivity and thermal resistance. There is no temperature region where the resistance changes suddenly, so the temperature uniformity of the plate is better than samples 4 to 7. It is.

[0073] Samples 1 to 7 satisfy the above requirement [5], and the temperature distribution and temperature drop rate are evaluated. The thermal conductivity of the joint is 0.7 (W / mK) at 25℃ and -60℃. If the temperature is above this, sufficient thermal conductivity can be obtained over a range from extremely low temperatures to room temperature.

[0074] Samples 1, 2, 4, and 5 contain aluminum nitride (AlN) as a filler. Samples 3, 6, and 7 contain alumina as a filler (Figure 4). Samples 1, 2, 4, and 5 have higher thermal conductivity and thermal resistance than samples 3, 6, and 7. The resistance is small (Figures 3, 9 to 11), and the temperature drop rate of the plate-shaped part is faster than 3, 6, and 7.

[0075] Samples 1, 3, 4, and 6 have a strain of 0.5 mm or more at maximum shear stress. The amount of strain under shear stress is an index of flexibility and stress relaxation performance. m or more, the flexibility and stress relaxation performance of the joint of the electrostatic chuck can be sufficiently ensured. This makes it possible.

[0076] <Consideration of methods for adjusting thermal conductivity> In order to prepare a material capable of forming the joint 40 of the above embodiment, the thermal conductivity of the forming material is adjusted. Specifically, the type of silicone resin (silicone adhesive) and the filler We created several samples with different types and ratios and measured the thermal conductivity. 1 Silicone resin is mainly composed of polydimethylsiloxane containing 5 mol% phenyl groups. The first silicone resin is made of a silicone resin mainly composed of polydimethylsiloxane. Silicone resin was used as the filler. Three types (15 μm, 5 μm, 2 μm) were used. First silicone resin, second silicone resin Both are silicone resins that can be cured and bonded by heating (silicone adhesive In addition to the main component, it contains known silane coupling agents and polydimethylsiloxane structures. It contains a crosslinking agent with the functional groups necessary for curing, a silicone curing catalyst, etc.

[0077] 13 and 14 are diagrams showing the composition and thermal conductivity of a sample using the first silicone resin. FIG. 15 shows a ternary diagram of the thermal conductivity of the sample using the first silicone resin. 6 and 17 are diagrams showing the composition and thermal conductivity of samples using the second silicone resin. FIG. 18 shows a ternary diagram of the thermal conductivity of the sample using the second silicone resin. In Fig. 18, the axis is the weight percentage, and the conductivity is shown next to the points. The thermal conductivity in Figures 4, 16, and 17 was measured using a thermal conductivity measuring device manufactured by C-THERM. The thermal conductivity shown in Figure 3 was measured using a thermal conductivity measurement The measurement was performed using the hot wire method (probe method) using the ARC-TC-1000 device. The relationship between the magnitude of the measurement results does not change because the mechanisms of determination are different, but the values ​​themselves are not necessarily No match.

[0078] The composition of sample S1 shown in FIG. 13 is identical to the compositions of samples 1 and 2 shown in FIG. In Fig. 13 and Fig. 14, the thermal conductivity of sample S1 is taken as the reference ("1"), and the thermal conductivity of the remaining samples is The conductivity is shown as the "thermal conductivity ratio." The composition of sample S18 shown in FIG. The composition of the sample S18 is consistent with that of the sample S4 and S5 shown in FIG. The thermal conductivity of the sample is taken as the reference ("1"), and the thermal conductivity of the remaining samples is taken as the "thermal conductivity ratio". It shows.

[0079] In FIG. 15, the thermal conductivity of 1.35 W / mK or more is circled. In FIG. In addition, in Figs. 15 and 18, As shown in the figure, whether the first silicone resin or the second silicone resin is used, The results showed that the thermal conductivity was higher when the ratio of 15um particles was high. The thermal conductivity is higher when 5um and 2um particles are added than when there are only particles. This is thought to be because small particles entered between large particles and became close to each other. .

[0080] Adhesives that do not change significantly in thermal conductivity have phase transition temperatures such as glass transition temperature and crystallization temperature. These adhesives are called silicone adhesives. This silicone adhesive contains 5 mol% phenyl groups. It is presumed that due to the large obstacles, the material does not crystallize even at low temperatures, is flexible, and the change in thermal conductivity is small. .

[0081] Silicone adhesives can be made more thermally conductive by adding inorganic fillers. In order to achieve derivatization, it is necessary to mix a large amount of filler, but the shape of the filler that can be mixed in large amounts is true. Spherical or granular. Rod, plate, or needle shapes have low fluidity, so they should be mixed in large amounts. It is difficult to apply adhesive to a small amount of material, and the hardness of the adhesive increases even in small amounts. It cannot be used to join materials with different modulus.

[0082] In order to increase the thermal conductivity of adhesives containing fillers, the shape of the fillers should be smaller than spherical. It is more preferable that the particles of the filler are in contact with each other or as close as possible to each other. In the case of granular materials, there are some protrusions and depressions, so the particles may be in contact with each other. This is thought to be due to increased contact with children.

[0083] From the viewpoint of increasing the thermal conductivity of the adhesive, it is preferable that the adhesive contains an aromatic functional group. The one containing aromatic functional groups has a higher density, and when mixed at the same weight ratio, the volume ratio The content in the polymer is thought to be due to the decrease in resin and the increase in filler. Aromatic groups have higher thermal conductivity due to pi bonds than sigma bonds in ethyl siloxanes. In addition, aromatic groups are thought to be highly oxidized by the aluminum in alumina and aluminum nitride. It can coordinate with metal atoms such as ruthenium and phosphorus atoms contained in surface treatment agents. This reduces the thermal resistance at the interface between the filler and adhesive, contributing to an overall increase in thermal conductivity. It is also possible that...

[0084] B. Second embodiment: FIG. 19 is a cross-sectional view illustrating a schematic configuration of an electrostatic chuck 10A according to the second embodiment. 20 is an enlarged view of the X portion in FIG. 19. The electrostatic chuck 10A according to the second embodiment has In addition to the electrostatic chuck 10 of the first embodiment, a terminal through hole 60 (FIG. 19) is provided. In the electrostatic chuck 10A of the present embodiment, the parts common to the electrostatic chuck 10 of the first embodiment are The terminal through-holes 60 are also simply referred to as "holes."

[0085] As shown in FIG. 19, the terminal through hole 60 penetrates the base portion 30A and the joint portion 40A. In the plate-shaped portion 20A, the terminal through hole 60 extends to below the chucking electrode 22. An electrode terminal 62 is disposed on the upper surface of the substrate 21 and is electrically connected to the chucking electrode 22 through a via 72 .

[0086] Specifically, as shown in FIG. 20, the plate-shaped portion 20A is connected to the chucking electrode 22 through a via 72. In this embodiment, the electrode pads 74 are arranged in the Z-axis direction. The electrode pad 74 and the via 72 are made of a conductive material (e.g., It is made of materials such as tungsten and molybdenum.

[0087] A columnar electrode terminal extending in the Z-axis direction is inserted into the terminal through hole 60 formed in the base portion 30A. In this embodiment, a cross section of the electrode terminal 62 (a cross section parallel to the surface direction) The upper end of the electrode terminal 62 reaches the electrode pad 74. is joined to the electrode pad 74 by a joint made of, for example, a metallic brazing material.

[0088] The electrode terminal 62 disposed in the terminal through hole 60 of the base portion 30A and the base portion 30A In order to insulate the terminals from each other, an insulating portion 64 is disposed in the terminal through hole 60 of the base portion 30A. The insulating portion 64 is disposed between the electrode terminal 62 and the surface of the terminal through hole 60. The insulating portion 64 is made of, for example, resin, ceramics, etc. In this embodiment, the thermal conductivity of the insulating portion 64 is A (i.e., the thermal conductivity of the plate-shaped portion 20A is lower than the thermal conductivity of the insulating portion 64). In addition, the area around the insulating portion 64, specifically, between the insulating portion 64 and the electrode terminal 62, Between the insulating portion 64 and the plate-shaped portion 20A, and between the insulating portion 64 and the base portion 30A, hole joints are provided. The hole joint 66 is made of the same material as the joint 40A. The insulating portion 64 is joined to the electrode terminal 62, the plate-shaped portion 20A, and the base portion 30A. In detail, the hole joint portion 66 is formed on the insulating portion 64 with respect to the second surface 26 of the plate-shaped portion 20A. The hole joint 66 is connected to the joint 40. The portion of the base portion 30A where the terminal through hole 60 is located has a low thermal conductivity. Therefore, this tends to cause a temperature difference in the temperature distribution of the plate-shaped portion 20A. The thermal conductivity of the material constituting the joint 40A is different from that of the material constituting the base portion 30A. Since the material is lower, the hole joint 66 is made thinner than the joint 40A to reduce the decrease in thermal conductivity. This suppresses the risk of temperature differences occurring.

[0089] The configuration for supplying power to the attraction electrode 22 is as described above. When the electrostatic chuck 10 is used, The chucking electrode 22 is connected to the electrode terminal 62, the electrode pad 74 and the via hole 76 from a power source (not shown). A voltage is applied via a conductive path that leads to the chucking electrode 22 via the electrode 72. An electrostatic attractive force is generated to attract and fix the wafer W to the attraction surface S1.

[0090] In the terminal through hole 60, the insulating part is fixed by using a resin adhesive such as a general silicone adhesive. When the plate-shaped portion 2 is joined to the electrostatic chuck 10A, the adhesive has poor thermal conductivity. At 0A, the heat dissipation performance of the portion corresponding to the terminal through hole 60 is reduced, and the first There is a risk that the temperature unevenness on the surface 24 will become large. According to the chuck 10A, the chuck 10A is made of the same material as the joint 40A and has a hole with good thermal conductivity. The portion of the plate-shaped portion 20A corresponding to the terminal through hole 60 can be dissipated heat via the terminal joint 66. As a result, the non-uniformity in the temperature of the plate-shaped portion 20A can be further suppressed.

[0091] The present disclosure is not limited to the above-described embodiments, and may be modified without departing from the spirit and scope of the present disclosure. For example, the above-mentioned embodiments described in the Summary of the Invention can be realized in various configurations. The technical features in the embodiments corresponding to the technical features solve some or all of the above problems. In order to achieve some or all of the above effects, the following may be replaced or recombined as appropriate. In addition, the technical features are not essential in this specification. If it is not explained in the text, it may be deleted as appropriate.

[0092] The present disclosure can also be realized in the following application examples. [Application example 1] A holding device for holding an object, A plate-like plate having a first surface on which the object is placed and a second surface opposite to the first surface. and a plate-shaped portion formed on the The plate-shaped portion is disposed on the second surface side of the plate-shaped portion, and the plate-shaped portion is supported by the plate-shaped portion. The plate-shaped portion has a cooling function. A base portion formed; The plate-shaped portion and the base portion are disposed between the plate-shaped portion and the base portion, and the plate-shaped portion and the base portion are joined together. A joint, Equipped with The thermal resistance of the junction is 1.1 x 10 at -60°C. -3 (m 2 K / W) or less Characterized by: holding device. [Application example 2] The holding device according to Application Example 1, The joint is When the thermal conductivity at -60℃ is λ1 and the thermal conductivity at 25℃ is λ2, λ 1 / λ2 is 1.18 or less, and When the thermal resistance at -60℃ is θ1 and the thermal resistance at 25℃ is θ2, then θ1 / θ2 is 0.85 or more, The present invention is characterized in that at least one of the following is satisfied: holding device. [Application example 3] The holding device according to Application Example 1 or Application Example 2, The thermal resistance of the junction at 25°C is 1.2×10 -3 (m 2 K / W) or less Characterized by: holding device. [Application example 4] The holding device according to any one of Application Examples 1 to 3, The joint has a thermal conductivity of 0.7 (W / mK) or more at 25°C and -60°C. Characterized in that holding device. [Application example 5] The holding device according to any one of Application Examples 1 to 4, The bonding portion contains aluminum nitride (AlN). holding device. [Application Example 6] The holding device according to any one of Application Examples 1 to 5, The strain amount at the maximum shear stress of the joint is 0.5 (mm) or more. R, holding device. [Application Example 7] The holding device according to any one of Application Examples 1 to 6, a hole penetrating the base portion; an insulating portion covering an inner wall of the hole; The insulating portion has an end surface facing the second surface of the plate-shaped portion and is joined to the plate-shaped portion. a hole joint; having The hole joint is made of the same material as the material constituting the joint, and and is thinner than the joint portion. holding device. [Explanation of symbols]

[0093] 10, 10A...Electrostatic chuck 20, 20A…Plate-shaped part 22...Adsorption electrode 24...Side 1 26…Second side 30, 30A...Base section 32... Coolant flow path 40, 40A...joint 50…Gas supply line 52…Gas outlet 60...Through hole for terminal 62...Electrode terminal 64…Insulation section 64S…end face 66…hole joint 70...Test piece 72…Beer 74...Electrode pad 80…Aluminum plate W…wafer

Claims

1. A holding device for holding an object, A plate-shaped portion having a first surface on which the object is placed and a second surface that is the reverse side of the first surface; a base portion formed in a plate shape, the base portion being disposed on the second surface side of the plate portion, supporting the plate portion, and having a cooling function; a joint portion disposed between the plate-shaped portion and the base portion and joining the plate-shaped portion and the base portion; Equipped with the joint includes an adhesive formed of a resin material, The thermal resistance of the junction is 1.1×10 at −60° C. -3 (m 2 K / W) or less, The thermal conductivity of the joint is 0.92 (W / mK) or more at −60° C., moreover, The joint is When the thermal conductivity at -60°C is λ1 and the thermal conductivity at 25°C is λ2, λ1 / λ2 is 1.18 or less; and When the thermal resistance at -60°C is θ1 and the thermal resistance at 25°C is θ2, θ1 / θ2 is 0.85 or more. At least one of the following is satisfied: The resin material is The silicone resin is characterized in that it is mainly composed of a phenyl group-containing polydimethylsiloxane. holding device.

2. 2. The holding device according to claim 1, The thermal resistance of the junction is 4.59×10 at −60° C. -4 (m 2 K / W) or more. holding device.

3. 2. The holding device according to claim 1, The thermal resistance of the joint at 25° C. is 1.2×10 -3 (m 2 K / W) or less. holding device.

4. A holding device as claimed in claim 3, The thermal resistance of the joint at 25° C. is 5.05×10 -4 (m 2 K / W) or more. holding device.

5. A holding device according to any one of claims 1 to 4, The joint has a thermal conductivity of 0.7 (W / mK) or more at 25°C and -60°C. holding device.

6. A holding device according to any one of claims 1 to 4, The bonding portion contains aluminum nitride (AlN). holding device.

7. A holding device according to any one of claims 1 to 4, The strain amount at maximum shear stress of the joint is 0.5 (mm) or more. holding device.

8. A holding device according to any one of claims 1 to 4, a hole penetrating the base portion; an insulating portion covering an inner wall of the hole; a hole joint portion that joins an end surface of the insulating portion facing the second surface of the plate-shaped portion and the plate-shaped portion; having The hole joint is formed of the same material as the material constituting the joint, and is thinner than the joint. holding device.

Citation Information

Patent Citations

  • Bonding structure of electrostatic chuck

    JP1992287344A

  • Part for semiconductor manufacturing device, and method for manufacturing the same

    JP2014207374A

  • Holding device

    JP2020068219A